Analysis of the Relationship Between Academic Supervision and the Transformational Leadership Model of School Principals in the Elementary School Pelabuhanratu Sukabumi on Teacher Performance - Yuya Yulianti; Suroyo Suroyo; Tita Rosita (EduLine: Journal of Education and Learning Innovation, 2024)
The purpose of this study was to determine how academic supervision and the principal's transformational leadership model affect teacher performance in Elementary School Pelabuhanratu Sukabumi. This study used a correlational quantitative method, associative type. This study involved all teachers in the Elementary School Pelabuhanratu sub-district, consisting of 435 teachers. The sample was 79 teachers, with an additional 10% to anticipate dropouts, totaling 87 teachers. This study used questionnaires and observation. According to the findings of this study, it was found that (1) It is known that the Sig. (2-tailed) between academic supervision and teacher performance is 0.005<0.05, indicating that there is a significant correlation between the variables of academic supervision and teacher performance; (2) It is known that the Sig. (2-tailed) between academic supervision and teacher performance is 0.005<0.05, and (3) it is known that the result of the R Square value is 0.849 or equal to 84.9%, which means that the academic supervision variable (X1) and the transformational leadership variable (X2) simultaneously (together) affect the teacher performance variable (Y) by 84.9%. In comparison, the rest (100% - 84.9% = 15.1%) is influenced by other variables outside the regression equation or variables not studied